EARLY IMPAIRMENTS OF RENAL FUNCTION AND CLINICAL INDICATORS: A CASE OF CHRONIC GLOMERULONEPHRITIS - Jumaniyazov B.K; Sapayeva Z.A; Matyakubova L.Sh. (Scholar Express Journals, 2025)
This article is dedicated to the identification of early impairments in renal function and their clinical significance in chronic glomerulonephritis (CGN). Chronic glomerulonephritis is a serious disease affecting the kidneys and other organs, and its early detection can help preserve renal function. The study explores effective methods for early diagnosis of CGN using clinical and laboratory indicators such as arterial hypertension, peripheral edema, proteinuria, estimated glomerular filtration rate (eGFR), and podocyte markers. The results offer innovative approaches based on biomarkers that can be applied in clinical practice for early diagnostics.
Keywords: Chronic glomerulonephritis; renal function; early diagnosis